Afectación de los procesos comunicativos de orden corporal en el contexto de aprendizaje por la mediación tecnológica. - Arias Obando, Daniela (Revista Miradas)
Within the educational context of today's society, one of the greatest shortcomings that can be glimpsed corresponds to the communicative processes within learning environments. This problem, enhanced by a world that is increasingly turning towards the digital, the individual and the virtual. It has generated a change that although gradual can be transcendental in the history of humanity, since we go from being socially active and face-to-face, developed in a context that was based on orality and sharing with individuals, to a society characterized by sharing from a distance, the digital, the virtual. This article analyses how body order communicative processes are affected during learning in the context of youth training at SENA, due to the use of technological mediations. The research, had a mixed approach, allowed a qualitative analysis of the affectations that were generated in the development of body language when technology was used in the training processes. In addition, identifying each non-verbal behaviour in the exercises that required the use of the Body; and from the quantitative analysis the frequency of the use of these non-verbal expressions was identified. The work was non-experimental, cross-sectional, based on the collection of data from participant observation of 9 face-to-face classes, statistical data recording of 44 videos and audio-visual review of 36 virtual classes. In this, the main conclusion shows that the use of technology does limit and affect the development of body language when it is used in its entirety in educational scenarios and not as a support tool in face-to-face scenarios.